Complete First Certificate: teacher's book - Brook-Hart G. Guy (Cambridge, Cambridge University Press, 2009)
Complete First Certificate is a brand new course for the revised First Certificate exam. It combines the very best in contemporary classroom practice with stimulating topics aimed at teenagers and young adults. The course covers every part of the First Certificate exam in detail providing preparation, practice, information and advice to ensure that students are fully prepared for every part of the exam. Informed by the Cambridge Learner Corpus and providing a complete FCE exam paper specially prepared for publication by Cambridge ESOL, Complete First Certificate is the most authentic exam preparation course available. Complete First Certificate Student's Book: contains 16 topic-based units. Each unit covers one part of each First Certificate paper. is informed by the Cambridge Learner Corpus to help students tackle typical First Certificate problem areas. includes a complete model exam paper supplied by Cambridge ESOL. includes a CD-ROM for self-study. provides Writing and Speaking reference sections dedicated to the Writing and Speaking papers contains a comprehensive Grammar reference section.